Black polyimide film as well as preparation method and application thereof
By adjusting the polymerization degree and thermal expansion coefficient of the polyimide film, the problem of poor dimensional stability of the existing black polyimide film is solved, and the dimensional stability and comprehensive performance are improved under high temperature conditions.
Patent Information
- Application Number
- CN202411662489.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing intrinsic black polyimide films have poor dimensional stability, resulting in the possible CTE mismatch under high temperature conditions.
By adjusting the polymerization degree and linear thermal expansion coefficient of the polyimide, a polyimide film with a polymerization degree of 10-300 was prepared, with a linear thermal expansion coefficient of between 20-25 ppm·K-1 to ensure that it is between 50- It has good dimensional stability within the temperature range of 250℃.
The good dimensional stability of the black polyimide film is achieved, ensuring that its performance remains consistent under high temperature conditions, avoiding the reliability problems caused by CTE mismatch, and maintaining excellent light-shielding characteristics, thermal stability and mechanical properties.
Smart Images

Figure CN119463176A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a black polyimide film and a preparation method and application thereof. Background Art
[0002] As the basic substrate or cover film of flexible printed circuit boards (FPCs), black polyimide (PI) films play an important role in industries such as optics, microelectronics, and aerospace, especially in applications that require blocking light. These materials are highly regarded for their excellent dimensional stability, mechanical strength, and thermal resistance, while minimizing light transmittance, which is essential for protecting circuit design intellectual property. In the aerospace field, black polyimide films have broad application prospects because they are able to maintain their performance under extreme temperature conditions while providing the required electrical insulation and light-shielding properties. In the optical and microelectronics industries, the low transparency characteristics of black polyimide films help improve the performance and reliability of equipment, especially in sensitive optical instruments and microelectronic components that need to shield external light interference. In addition, as the FPC market continues to grow, the demand for black films with excellent electrical properties and outstanding light-shielding capabilities is also increasing, which has promoted the research and development of such materials.
[0003] The preparation method of black polyimide film involves the use of specific raw materials and high-temperature imidization process, which can achieve excellent light-shielding and mechanical properties while maintaining the thermal stability and dimensional stability of the material. In terms of manufacturing process, studies have been conducted to add carbon black and manganese dioxide to polyimide films by in-situ doping methods to enhance the opacity of the film. By optimizing the ratio and doping amount of fillers, black polyimide films with ultra-high electrical properties can be obtained, which has potential application value for electronic equipment and the semiconductor industry. In addition, by introducing nano-silica particles and long-chain organic additives during the preparation of polyimide films, the mechanical properties of the film can be improved while maintaining the intrinsic black color and good light-shielding properties. Such improved mechanical properties are crucial for the durability and reliability of the film in practical applications.
[0004] In the field of materials science, improving the intrinsic properties of black polyimide films by adjusting the repeating unit structure is an effective way to explore the potential of materials. Although the performance can be enhanced by introducing other components, it is undoubtedly a challenging task to achieve a comprehensive improvement in comprehensive performance while maintaining the key characteristic of low transparency. The design and preparation of intrinsic black polyimide films not only involves the chemical structure of the material, but also its performance in multiple aspects such as optics, mechanics and thermals.
[0005] Prior art Polymers (Basel). 2022;14(18)3881 reported a black polyimide film with good light-shielding properties. However, the dimensional stability of the BPI-6 film in the article was poor, and the linear thermal expansion coefficient CTE value in the temperature range of 50-250°C was 34.8×10 -6 / K. In FPCB manufacturing, the CTE value of copper foil is 17.0×10 -6 / K, and the PI film and substrate should have similar CTE values. However, the CTE value of BPI-6 film is too different from that of copper foil, which may cause reliability problems caused by CTE mismatch.
[0006] Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defect of poor dimensional stability of the existing intrinsic black polyimide film, and the present invention provides a black polyimide film and a preparation method and application thereof. The black polyimide film of the present invention has a good linear thermal expansion coefficient and good dimensional stability while ensuring good light-shielding properties, thermal stability, heat resistance and mechanical properties.
[0008] The present invention solves the above technical problems through the following technical solutions.
[0009] The present invention provides a polyimide having a structure as shown in Formula I,
[0010] ;
[0011] in,
[0012] The degree of polymerization of the polyimide is 10-300;
[0013] The linear thermal expansion coefficient of the polyimide is 20-25 ppm·K -1 .
[0014] In a certain embodiment, the degree of polymerization of the polyimide is 20-260.
[0015] In one embodiment, the linear thermal expansion coefficient of the polyimide is 22-23 ppm·K -1 , for example 22.17ppm·K -1 .
[0016] In a certain embodiment, the linear thermal expansion coefficient of the polyimide is obtained by testing using the following method:
[0017] 1. Test sample: Make sure the sample thickness is 20 to 40 microns and the sample area is 0.5 cm 2To 1cm 2 ;
[0018] 2. Test equipment: TMA instrument (e.g. NETZSCH TMA 402F3 thermomechanical analyzer);
[0019] 3. Test conditions: heating rate is constant 5°C / min, test atmosphere is nitrogen;
[0020] 4. Start the test: The instrument heats the sample according to the set conditions and records the position change of the probe as the temperature changes;
[0021] 5. Data collection and analysis: Calculate the linear thermal expansion coefficient using the following formula:
[0022]
[0023] in, is the change in sample length, is the initial length, is the temperature change;
[0024] Plotting curve: Sample size change ( ) and temperature ( ) from this curve, select the 50-250℃ area and calculate the slope, which is the linear thermal expansion coefficient.
[0025] In one embodiment, the number average molecular weight of the polyimide is (1×10 4 )~(10×10 4 ) g / mol, preferably (2×10 4 )~(3×10 4 ) g / mol, more preferably 2.74×10 4 g / mol.
[0026] In one embodiment, the weight average molecular weight of the polyimide is (1×10 4 )~(20×10 4 ) g / mol, preferably (8×10 4 )~(10×10 4 ) g / mol, more preferably 9.03×10 4 g / mol.
[0027] In one embodiment, the molecular weight distribution of the polyimide is 2-5, preferably 3-3.5, for example 3.3.
[0028] The present invention provides a method for preparing a polyimide having a structure represented by the above formula I, which comprises the following steps:
[0029] 1) In an amide solvent, in the presence of an inert gas, 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II and 4,4'-diaminodiphenylamine represented by formula III are subjected to a polymerization reaction as shown below to obtain a solution containing a compound represented by formula IV;
[0030] ;
[0031] 2) coating the solution containing the compound represented by formula IV obtained in step 1), removing the solvent, and then heating to carry out an imidization reaction as shown below to obtain a polyimide having a structure represented by formula I;
[0032] ;
[0033] in,
[0034] The definition of n is as described above.
[0035] In one embodiment, in step 1), the inert gas may be nitrogen, helium, neon or argon, preferably nitrogen.
[0036] In one embodiment, in step 1), the amide solvent may be N,N'-dimethylformamide or N,N'-dimethylacetamide, preferably N,N'-dimethylformamide.
[0037] In one embodiment, in step 1), the polymerization reaction temperature is 10-25 °C.
[0038] In one embodiment, in step 1), the polymerization reaction time can be monitored by conventional means in the art (for example, by color, the reactant changes from a precipitate to a brown solution), and the polymerization reaction time can be 18-30 hours, preferably 24 hours.
[0039] In one embodiment, in step 1), the molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II to 4,4'-diaminodiphenylamine represented by formula III may be (0.8-1.2):1, preferably 1:1.
[0040] In a certain scheme, in step 1), the mass ratio of the total mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II and 4,4'-diaminodiphenylamine represented by formula III to the amide solvent can be a conventional mass ratio in the art, for example, 1:(5-10), preferably 1:(6-8).
[0041] In one embodiment, in step 1), the materials for the polymerization reaction are: the amide solvent, the inert gas, the 3,3',4,4'-biphenyltetracarboxylic dianhydride of formula II and the 4,4'-diaminodiphenylamine of formula III;
[0042] The amide solvent is preferably N,N'-dimethylformamide;
[0043] The inert gas is preferably nitrogen.
[0044] In a certain scheme, step 1) includes the following steps: in the presence of an inert gas, 3,3',4,4'-biphenyltetracarboxylic dianhydride shown in formula II is added to a mixed solution of 4,4'-diaminodiphenylamine and N,N'-dimethylformamide shown in formula III, N,N'-dimethylformamide is then added to the mixed solution to adjust the solid content to 12-18 wt% (preferably 15 wt%), and a polymerization reaction is carried out to obtain a solution containing the compound shown in formula IV.
[0045] In a certain solution, in step 2), the coating may be conventional coating in the art, for example, coating on a glass substrate.
[0046] In one embodiment, in step 2), the solvent removal may be carried out by conventional methods for removing solvents in the art, such as heating to remove the solvent;
[0047] Preferably, the temperature of heating to remove the solvent may be 60-100°C, preferably 80°C;
[0048] Preferably, the time for heating to remove the solvent is 0.5 to 2 hours, preferably 1 hour.
[0049] In one embodiment, in step 2), the heating temperature may be a conventional heating temperature in the art, for example, 100-350°C, preferably 100-300°C.
[0050] In one embodiment, in step 2), the heating time may be a conventional heating time in the art, for example, 4 to 8 hours, preferably 6 hours.
[0051] In one embodiment, in step 2), the heating may be a conventional heating method in the art, such as gradient heating.
[0052] In a certain scheme, in step 2), the above-mentioned gradient heating can be segmented heating at 100-350°C for 4 to 8 hours; the above-mentioned gradient heating is preferably heated at 100-140°C for 1 to 3 hours, then heated at 180-220°C for another 1 to 3 hours, and finally heated at 280-350°C for another 1 to 3 hours; the above-mentioned gradient heating is more preferably heated at 120°C for 2 hours, then heated at 200°C for another 2 hours, and finally heated at 300°C for another 2 hours.
[0053] In a certain scheme, step 2) includes the following steps: coating the solution containing the compound represented by formula IV obtained in step 1) on a glass substrate, heating at 60-100°C for 0.5-2 hours to remove the solvent, then heating at 100-140°C for 1-3 hours, then heating at 180-220°C for another 1-3 hours, and finally heating at 280-350°C for 1-3 hours to carry out an imidization reaction to obtain a polyimide having a structure represented by formula I.
[0054] The present invention also provides a polyimide, which is prepared by the preparation method of the polyimide having the structure shown in the above formula I.
[0055] The present invention also provides a polyimide film, which comprises a polyimide having a structure shown in the above formula I.
[0056] The present invention also provides an application of the polyimide having the structure shown in the above formula I or the above polyimide film as an FPC material.
[0057] In the present invention, unless otherwise specified, "room temperature" refers to 10-25°C.
[0058] In the present invention, unless otherwise specified, "°C" means Celsius.
[0059] In the present invention, unless otherwise specified, "h" means hours.
[0060] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0061] The reagents and raw materials used in the present invention are commercially available.
[0062] The positive improvement effect of the present invention is that the film of the present invention has a good linear thermal expansion coefficient and good dimensional stability while ensuring good light-shielding properties, thermal stability, heat resistance and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 This is a flow chart of the synthesis and preparation of the black polyimide film in Example 1.
[0064] Figure 2 This is the infrared spectrum of the black polyimide film synthesized in Example 1.
[0065] Figure 3 This is the TGA spectrum of the black polyimide film synthesized in Example 1.
[0066] Figure 4 This is the UV-visible spectrum of the black polyimide film synthesized in Example 1.
[0067] Figure 5 This is the TMA spectrum of the black polyimide film synthesized in Example 1.
[0068] Figure 6 This is the DMA spectrum of the black polyimide film synthesized in Example 1.
[0069] Figure 7 This is the tensile (stress-strain) curve of the black polyimide film synthesized in Example 1. DETAILED DESCRIPTION
[0070] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0071] The structure of the black polyimide film synthesized by the present invention is characterized by infrared spectroscopy (FTIR). Fourier transform infrared spectroscopy (FT-IR) analysis uses a Nicolet 6700 Fourier transform infrared spectrometer from NICOLET, USA, a KBr tablet method, and a scanning range of 4000-400 cm -1 , resolution 0.09cm -1 , scan times 32 times.
[0072] Example 1: Synthesis of black polyimide film BPDA-NDA
[0073] (1) In a nitrogen atmosphere, add 2.00 g (10.05 mmol) of 4,4'-diaminodiphenylamine to a flame-dried 100 mL three-necked round-bottom flask equipped with a mechanical stirrer, a constant pressure dropping funnel and a nitrogen inlet. Slowly add 20 mL of N,N'-dimethylformamide through the constant pressure dropping funnel. After 4,4'-diaminodiphenylamine is completely dissolved, add 2.93 g (10.05 mmol) of 3,3',4,4'-biphenyltetracarboxylic dianhydride. Slowly add 20 mL of N,N'-dimethylformamide through the constant pressure dropping funnel. Adjust the solid content to about 15% (weight ratio). Stir at room temperature for 24 h under nitrogen protection to form a viscous polyamic acid (PAA) solution. The number average molecular weight of the obtained PPA is 2.96×10 4 g / mol, and the weight average molecular weight is 9.74×10 4 g / mol, and the molecular weight distribution is 3.29.
[0074] (2) The polyamic acid (PAA) solution is evenly coated on the glass substrate to form a uniform coating. The coated glass plate is then subjected to an initial heat treatment at 80°C for 1 hour to help the solvent evaporate. A temperature-controlled heating program is then performed, first heating at 120°C for 2 hours, then heating at 200°C for another 2 hours, and finally heating at 300°C for another 2 hours to complete the imidization of the polyamic acid (PAA). The resulting polyimide film has a thickness ranging from 20 to 40 μm, a degree of polymerization (n) of 20-260, and a number average molecular weight of 2.74×10 4 g / mol, weight average molecular weight is 9.03×10 4 g / mol, and the molecular weight distribution is 3.30.
[0075] Figure 1 This is a schematic diagram of the process of synthesizing the black polyimide film BPDA-NDA in Example 1.
[0076] Figure 2 This is the infrared spectrum (FTIR) of the black polyimide film BPDA-NDA synthesized in Example 1. Figure 2 It can be seen that 1780 cm -1 and 1720 cm -1 The peak at 1360 cm is attributed to the stretching vibration of the carbonyl group (C=O) in the imide ring. -1 The peak at 2500-3600 cm-1 was assigned to the CN bond absorption characteristic of the imide ring. -1The absence of significant peaks in the range that are usually associated with -COOH and -CONH groups indicates that the polyimide film has been fully imidized. These observations confirm the successful synthesis of the polyamic acid precursor and the preparation of the fully imidized polyimide film.
[0077] Test Example 1 Thermal Performance Test
[0078] The black polyimide film prepared in Example 1 was cut into sheets for thermogravimetric analysis. The thermogravimetric analysis (TGA) was performed using a PerkinElmer TGA 8000 thermogravimetric analyzer with a heating rate of 10°C / min, a temperature range of 40-600°C, and a nitrogen flow rate of 60 mL / min.
[0079] Figure 3 This is the TGA curve of the black polyimide film synthesized in Example 1 under nitrogen conditions. Figure 3 It can be seen that the film was subjected to thermogravimetric analysis under a nitrogen atmosphere, and the temperature for 5% weight loss was 474°C, and the residual rate at 600°C was 80.7%, indicating its good thermal stability.
[0080] Test Example 2: Light-shielding property test
[0081] The light transmittance of the black polyimide film prepared in Example 1 was tested. The light transmittance of the film was analyzed by ultraviolet-visible spectroscopy (UV-vis), using a Lambda950 ultraviolet-visible spectrophotometer from PerkinElmer, at room temperature, and in a measurement wavelength range of 200-800 nm.
[0082] Figure 4 This is the UV-visible spectrum of the black polyimide film BPDA-NDA synthesized in Example 1. Figure 4 It can be seen that the synthesized black polyimide film has good low transparency, and its transmittance is as low as 0.004% under visible light with a wavelength of 400nm. The highest transmittance is only 62.4%, indicating that it has good light-shielding properties.
[0083] Test Example 3 Dimensional stability test
[0084] The black polyimide film prepared in Example 1 was subjected to a dimensional stability test. The linear thermal expansion coefficient of the film was analyzed by thermomechanical analysis (TMA), using NETZSCH TMA 402F3 in a temperature range of 50-300°C.
[0085] 1. Sample preparation: For thin film samples, ensure that the sample has a certain thickness (20 to 40 microns) and area (0.5 to 1 cm2 );
[0086] 2. Set up the TMA instrument: Before testing, calibrate the TMA instrument according to the manufacturer's instructions to ensure accurate measurements;
[0087] 3. Define the test conditions: e.g. constant heating rate (5°C / min), test atmosphere (nitrogen);
[0088] 4. Start the test: The instrument heats the sample according to the set conditions and records the position change of the probe as the temperature changes;
[0089] 5. Data collection and analysis: Calculate the linear thermal expansion coefficient using the following formula:
[0090]
[0091] in, is the change in sample length, is the initial length, is the temperature change.
[0092] Plotting curve: Sample size change ( ) and temperature ( ). From this curve, select the 50-250℃ area and calculate the slope, which is the linear thermal expansion coefficient.
[0093] Figure 5 This is the TMA spectrum of the black polyimide film BPDA-NDA synthesized in Example 1. Figure 5 It can be seen that the synthesized black polyimide film has a low linear thermal expansion coefficient, which is as low as 22.17 ppm·K in the temperature range of 50-250°C. -1 , indicating its good dimensional stability.
[0094] Test Example 4 Heat resistance test
[0095] The heat resistance of the black polyimide film prepared in Example 1 was tested. The glass transition temperature of the film was analyzed by dynamic thermal mechanical analysis (DMA), which was performed using DMAQ800 from TA Instruments, with a nitrogen atmosphere, a heating rate of 5°C / min, a temperature range of 30-350°C, and a frequency of 1 Hz.
[0096] Figure 6 This is the DMA spectrum of the black polyimide film BPDA-NDA synthesized in Example 1. Figure 6 It can be seen that the synthesized black polyimide film has a higher glass transition temperature, reaching 319.5°C, indicating its good heat resistance.
[0097] Test Example 5 Mechanical Properties Test
[0098] The black polyimide film prepared in Example 1 was subjected to a mechanical property test. The mechanical properties of the film were analyzed using an electronic universal testing machine (UTM), the electronic universal testing machine (UTM) used was Instron 34TM-30, the tensile rate was 5 mm / min, and the test temperature was room temperature.
[0099] Figure 7 The tensile (stress-strain) curve of the black polyimide film synthesized in Example 1. Five specimens with a size of 150 mm × 10 mm were obtained by cutting. The tensile strength was determined to be 104.7 MPa by the average value of the results obtained from all the test specimens. The tensile strength of the specimen with the best performance was 117 MPa, indicating that it has excellent mechanical properties.
Claims
1. A polyimide having a structure as shown in formula I, ; in, The degree of polymerization of the polyimide is 10-300; The linear thermal expansion coefficient of the polyimide is 20-25 ppm·K -1 .
2. The polyimide having the structure represented by formula I according to claim 1, characterized in that: The polyimide having the structure shown in Formula I satisfies one or more of the following conditions: (1) The degree of polymerization of the polyimide is 20-260; (2) The linear thermal expansion coefficient of the polyimide is 22-23 ppm·K -1 ; (3) The number average molecular weight of the polyimide is (1×10 4 )~(10×10 4 ) g / mol; (4) The weight average molecular weight of the polyimide is (1×10 4 )~(20×10 4 ) g / mol; and (5) the molecular weight distribution of the polyimide is 2 to 5.
3. The polyimide having a structure as shown in formula I according to claim 1, characterized in that: The polyimide having the structure shown in Formula I satisfies one or more of the following conditions: (1) The linear thermal expansion coefficient of the polyimide is 22.17 ppm·K -1 ; (2) The number average molecular weight of the polyimide is (2×10 4 )~(3×10 4 ) g / mol; (3) The weight average molecular weight of the polyimide is (8×10 4 )~(10×10 4 ) g / mol; and (4) the molecular weight distribution of the polyimide is 3 to 3.
5.
4. The polyimide having a structure represented by formula I according to claim 1, characterized in that: The polyimide having the structure shown in Formula I satisfies one or more of the following conditions: (1) The number average molecular weight of the polyimide is 2.74×10 4 g / mol; (2) The weight average molecular weight of the polyimide is 9.03×10 4 g / mol; and (3) the molecular weight distribution of the polyimide is 3.
3.
5. A method for preparing a polyimide having a structure represented by formula I as described in any one of claims 1 to 4, comprising the following steps: 1) In an amide solvent, in the presence of an inert gas, 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II and 4,4'-diaminodiphenylamine represented by formula III are subjected to a polymerization reaction as shown below to obtain a solution containing a compound represented by formula IV; ; 2) coating the solution containing the compound represented by formula IV obtained in step 1), removing the solvent, and then heating to carry out an imidization reaction as shown below to obtain a polyimide having a structure represented by formula I; ; in, The definition of n is as described in any one of claims 1-4.
6. The method for preparing a polyimide having a structure represented by formula I according to claim 5, characterized in that: The preparation method meets one or more of the following conditions: (1) In step 1), the inert gas is nitrogen, helium, neon or argon, preferably nitrogen; (2) In step 1), the amide solvent is N,N'-dimethylformamide or N,N'-dimethylacetamide, preferably N,N'-dimethylformamide; (3) In step 1), the polymerization reaction temperature is 10-25°C; (4) In step 1), the polymerization reaction time is 18-30 hours, preferably 24 hours; (5) In step 1), the molar ratio of 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II to 4,4'-diaminodiphenylamine represented by formula III is (0.8-1.2):1, preferably 1:1; (6) In step 1), the mass ratio of the total mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II and 4,4'-diaminodiphenylamine represented by formula III to the amide solvent is 1:(5-10), preferably 1:(6-8); (7) In step 1), the materials for the polymerization reaction are: the amide solvent, the inert gas, the 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II and the 4,4'-diaminodiphenylamine represented by formula III; The amide solvent is preferably N,N'-dimethylformamide; The inert gas is preferably nitrogen; (8) In step 2), the coating is applied on a glass substrate; (9) In step 2), the solvent removal is performed by heating; Preferably, the temperature of heating to remove the solvent is 60-100°C, preferably 80°C; Preferably, the time for heating to remove the solvent is 0.5 to 2 hours, preferably 1 hour; (10) In step 2), the heating temperature is 100-350°C, preferably 100-300°C; (11) In step 2), the heating time is 4 to 8 hours, preferably 6 hours; and (12) in step 2), the heating is gradient heating; Preferably, the gradient heating is staged heating at 100-350°C for 4-8 hours; The gradient heating is preferably heated at 100-140°C for 1-3 hours, then heated at 180-220°C for another 1-3 hours, and finally heated at 280-350°C for another 1-3 hours; The gradient heating is more preferably heated at 120°C for 2 hours, then heated at 200°C for another 2 hours, and finally heated at 300°C for another 2 hours.
7. The method for preparing a polyimide having a structure represented by formula I according to claim 5, characterized in that: The preparation method meets one or two of the following conditions: (1) Step 1) comprises the following steps: in the presence of an inert gas, adding 3,3',4,4'-biphenyltetracarboxylic dianhydride represented by formula II to a mixed solution of 4,4'-diaminodiphenylamine represented by formula III and N,N'-dimethylformamide, further adding N,N'-dimethylformamide to the mixed solution to adjust the solid content to 12-18 wt% (preferably 15 wt%), and performing a polymerization reaction to obtain a solution containing the compound represented by formula IV; and (2) step 2) comprises the following steps: coating the solution containing the compound represented by formula IV obtained in step 1) on a glass substrate, heating at 60-100° C. for 0.5-2 hours to remove the solvent, then heating at 100-140° C. for 1-3 hours, then heating at 180-220° C. for another 1-3 hours, and finally heating at 280-350° C. for another 1-3 hours to carry out an imidization reaction, thereby obtaining a polyimide having a structure represented by formula I.
8. A polyimide prepared by the method for preparing a polyimide having a structure represented by formula I as described in any one of claims 5 to 7.
9. A polyimide film comprising a polyimide having a structure represented by formula I as claimed in any one of claims 1 to 4.
10. Use of a polyimide having a structure represented by formula I as claimed in any one of claims 1 to 4 or a polyimide film as claimed in claim 9 as an FPC material.
Citation Information
Patent Citations
Intrinsic black polyimide film, and preparation method and applications thereof
CN109180936A
Polyimide film having excellent high temperature stability and substrate for display device using the same
KR1020120073909A
Polyimide substrate and display substrate module comprising same
WO2017116103A1
Polyimide film and method for producing same
WO2024019587A1